The strategies for character building through sports participation - M.S. Omar-Fauzee; Mohd Nizam Nazarudin; Yudha M. Saputra; Nina Sutresna; Duangkrai Taweesuk; Wipoj Chansem; Rozita Abd. Latif; Soh, Kim Geok (Human Resource Management Academic Research Society (HRMARS), 2012)
The sport participation has been a major part of our life in the societies. Studies on sports participation have found that sports have both positive and negative influence on character buildings. It has been on-going debate on whether ‘sports build character’ but through literature analysis, author had found that ‘with the intention, sports do build character.’ Therefore, strategies of building character through sports are suggested in this paper.